Glucocorticoid-regulated glycoprotein maturation in wild-type and mutant rat cell lines (The Rockefeller University Press, 1986)
Glucocorticoid hormones can regulate the posttranslational maturation of mouse mammary tumor virus (MTV) precursor polyproteins in M1.54, a stably infected rat hepatoma cell line. We have used complement- mediated cytolysis to recover variants of M1.54 that fail to express MTV cell surface glycoproteins in a hormone-regulated manner (Firestone, G.L., and K.R. Yamamoto, 1983, Mol. Cell. Biol., 3:149- 160). One such clonal isolate, CR4, is similar to wild-type with respect to synthesis of MTV mRNAs, production of the MTV glycoprotein precursor (gPr74env) and a glycosylated maturation product (gp51), and hormone-induced processing of two MTV phosphoproteins. In contrast, three viral cell surface glycoproteins (gp78, gp70, and gp32) and one extracellular species (gp70s), which derive from gPr74env in glucocorticoid-treated wild-type cells, fail to appear in CR4. CR4 showed no apparent alterations in proliferation rate, cell shape, or expression of total functional mRNA and bulk glycoproteins. We conclude that the genetic lesion in CR4 defines a highly selective hormone- regulated glycoprotein maturation pathway that alters the fate of a restricted subset of precursor species.